Sinergi Pendidikan Agama Islam Dan Manajemen Pendidikan Islam Dalam Pembentukan Karakter Mahasiswa Berbasis Nilai Islami - Siti Muldiah; Dewi Wulandari (LPPM STAI La Tansa Mashiro, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping students' personalities and character based on Islamic values. In the context of higher education, character formation is not solely the responsibility of religious instruction but is also closely related to a planned, organized, and spiritually oriented educational management system. Synergy between Islamic Religious Education and Islamic Educational Management is crucial for creating an academic environment that emphasizes not only cognitive achievement but also the development of students' morals, ethics, and social responsibility. Through Islamic educational management, values ​​such as trustworthiness, discipline, honesty, and justice can be systematically internalized in the learning process and campus culture. This study aims to analyze how the integration of Islamic Religious Education principles and an Islamic managerial approach can strengthen students' holistic character formation. The method used was a literature review with a descriptive qualitative approach, focusing on the analysis of scientific literature, academic journals, and Islamic education policy documents from the past ten years. The study results indicate that the synergy between Islamic Religious Education (PAI) and Islamic Education Management (IED) can shape the character of students who are faithful, knowledgeable, and have noble morals through the management of educational institutions oriented towards the values ​​of monotheism and Islamic humanism. Thus, the collaboration between the two not only builds academic competence but also strengthens the spiritual and moral identity of students as future leaders with integrity in modern society.